Question

P) ( cos (alpha)+cos (alpha+2 theta)=cos (alpha+theta) )
- ( operatorname{doc} alpha+left[cos alpha cdot cos ^{2} theta-cos alpha cdot sin 2 theta-2 sin alpha cdot sin theta . cos thetaright] )
( =(cos alpha cdot cos theta-sin alpha cdot sin theta) )
7) ( cos alpha[1+cos 2 theta-sin 2 theta]-2 sin alpha sin theta cos theta=cos (x+theta) )
8) ( cos x cdot[2 cos 2 theta]-2 frac{sin alpha cdot cos theta cdot sin theta}{f}=cos (alpha+theta) )
( vec{z} )
( 2 cos theta[cos alpha cdot cos theta=sin alpha cdot sin theta]=cos (alpha+theta) )
2) ( cos theta=1 / 2 )
& ( theta=60^{circ}, 300^{circ} )

# Card - Cap (240) tlox (2420) 20

Solution